Development of a Module to Teach Basic Concepts of Interfacing and Connectivity in Internet of Things - Ayodele, Obasegun, Tekena (My University, 2018)
This paper presents a basic laboratory training module aimed at helping undergraduate students understand the interfacing and connectivity issues involved in the Internet of things (IoT). The training module uses a sequential teaching approach to draft quasi-experiments for teaching basic IoT concepts. Interfacing includes identification, embedded sensing and embedded actuating while connectivity includes wireless connectivity and web/ mobile services. An IoT function (control and/or measurement) is first selected by users based on the physical variable of interest and the action to be carried out. The user will also select a connectivity option based on network types and transmission technologies available for communication between a sensor and/or an actuator and a gateway. The available connectivity options in this work are Bluetooth and RF. An interface is then setup based on the choices made using Arduino Pro Mini as microcontroller. Arduino Yun and a smartphone are the available gateway options depending on the connectivity option of the interface. When Bluetooth is the connectivity type on the interface, the smartphone is used as gateway while Arduino Yun serves as the gateway when RF is the connectivity option on the interface. The training module is accompanied with an instruction manual which contains instructions on the set ups and short notes on signals and systems, Analog to Digital Converters (ADC), Digital to Analog Converters (DAC), Wireless Sensor Networks (WSN), etc. The training module was tested with 100 randomly selected students. A few students had problems setting up the interface correctly. Coding the Arduino boards was a challenge for some of the students while a few others had challenges with creating sensor nodes. Choosing the correct connectivity type to match a gateway was the most challenging for the students.
Supplemental Materials: https://osf.io/p9bsm/
Keywords: sensor; actuator; connectivity; interface; Internet of Things